مساهمة محافظ الحسابات في تحسين جودة القوائم والتقارير المالية - وليــــد بـــلال; محمد الهادي منصوري; المولدي كيرد; محمد عبد اللطيف زهواني (جامعة الوادي University Of Eloued, 2024)
"هدفت هذه الدراسة إلى معرفة مساهمة محافظ الحسابات في تحسين جودة القوائم والتقارير المالية، من خلال الدور المحوري والفعال الذي يلعبه محافظي الحسابات ويظهر دوره في المهام الموكلة إليه والدور الذي يلعبه في إضفاء المصداقية على المعلومات المحاسبية الواردة في القوائم المالية، التي تنشرها المؤسسات وذلك من خلال تقريره الذي يبدي فيه رأيه الفني المحايد على صحة وصدق وإنتظامية الحسابات السنوية ومدى شفافيتها وصدقها في التعبير عن الوضعية الحقيقية للمؤسسة. خلصت الدراسة إلى أن محافظ الحسابات له دور فعال في تحسين جودة القوائم والتقارير المالية، وذلك من خلال المصادقة على صحة وشرعية الحسابات، وبذلك يبرز الدور الفعال الذي يقوم به محافظ الحسابات ولتحقيق هذا الهدف، تم إستخدام المنهج الوصفي التحليلي المدعم بدراسة ميدانية لدى مكتب محافظ حسابات، تمثلت في التطرق للخطوات العملية لمحافظ الحسابات في أداء مهمته وتحليل التقرير النهائي لشركة خاصة تنشط في مجال الأشغال العمومية الكبرى والري وتوصلت الدراسة للنتائج التالية: * يمتلك محافظ الحسابات الكفاءة العلمية والعملية المطلوبة بالإضافة إلى الخبرة المهنية التي تمكنه من إبداء رأي فني محايد حول مصداقية المعلومات المحاسبية الواردة بالقوائم المالية؛ * تتمتع المعلومات المحاسبية بمصداقية عالية، من خلال إستخدام أساليب معينة للقياس والإفصاح يمكن أن يتوصل إليها شخص آخر بإستخدام نفس الأساليب التي تتمثل في الجرد الفعلي للأصل وفحص كل ما من شأنه أنه يثبت وجود وملكية الأصل، والتأكد من صحة وسلامة ودقة البيانات المحاسبية المقيدة في الدفاتر ومدى الإعتماد عليها والتأكد من جودة التقارير المالية والمعلومات المحاسبية والإفصاح والشفافية في تلك القوائم المالية؛ * يبرز دور محافظ الحسابات الفعال والرئيسي في فحص مصداقية المعلومات المحاسبية الواردة في القوائم المالية حيث يعلم محافظ الحسابات المسيرين والجمعية العامة بكل نقص قد يكتشفه أو اطلع عليه في مصداقية المعلومات المحاسبية بالقوائم المالية وذلك من خلال فحص محافظ الحسابات لصحة ومصداقية الحسابات السنوية والقوائم المالية ومطابقتها للمعلومات المحاسبية؛ * إن الحصول على القوائم المالية ليس هدفا في حد ذاته وإنما وسيلة للحصول على المعلومات المحاسبية والنتائج للإستفادة بها في أخذ القرارات والحكم على نتائج عمليات المؤسسة ومركزها المالي. " "This study aimed to know the contribution of the portfolio of accounts in improving the quality of financial statements and reports, through the pivotal and effective role played by the governors of accounts and shows his role in the tasks entrusted to him and the role he plays in giving credibility to the accounting information contained in the financial statements, published by institutions through his report in which he expresses his neutral technical opinion on the correctness, honesty and regularity of annual accounts and the extent of transparency and honesty in Express the real status of the institution. The study concluded that the portfolio of accounts has an effective role in improving the quality of financial statements and reports, by approving the validity and legitimacy of accounts, and thus highlights the effective role played by the portfolio of accounts and to achieve this goal, the descriptive analytical approach supported by a field study was used at the Office of the Governor of Accounts, represented in addressing the practical steps of the portfolios of accounts in the performance of its mission and analyzing the final report of a private company active in the field of major public works and irrigation, and the study reached the following results: * The auditor possesses the required scientific and practical competence in addition to the professional experience that enables him to express an impartial technical opinion on the reliability of the accounting information contained in the financial statements؛ * Accounting information enjoys high credibility, through the use of certain methods of measurement and disclosure that another person can arrive at using the same methods, which are the actual inventory of the asset, examining everything that would prove the existence and ownership of the asset, and ensuring the validity, integrity and accuracy of the accounting data recorded in the books and the extent of Reliance on it and ensuring the quality of financial reports, accounting information, disclosure and transparency in those financial statements ؛ * The effective and main role of the accounts governor is highlighted in examining the credibility of the accounting information contained in the financial statements, as the accounts governor informs the managers and the General Assembly of every deficiency that he may discover or see in the credibility of the accounting information in the financial statements, through the accounts governor’s examination of the validity and credibility of the annual accounts and financial statements and their conformity with the accounting information * Obtaining financial statements is not a goal in itself, but rather a means of obtaining accounting information and results to benefit from in making decisions and judging the results of the organization’s operations and financial position. "
مذكرة ماستر
Keywords: محافظ الحسابات – القوائم المالية – المعلومات المحاسبية; Auditor – Financial Statements – accounting Information